Values in Science: The Case of Scientific Collaboration. Issue 2 (April 2015) - Rolin, Kristina
Abstract : Much of the literature on values in science is limited in its perspective because it focuses on the role of values in individual scientists' decision making, thereby ignoring the context of scientific collaboration. I examine the epistemic structure of scientific collaboration and argue that it gives rise to two arguments showing that moral and social values can legitimately play a role in scientists' decision to accept something as scientific knowledge. In the case of scientific collaboration some moral and social values are properly understood to be extrinsic epistemic values, that is, values that promote the attainment of scientific knowledge.